Aquivion Perfluorosulfonic Superacid as an Efficient Pickering Interfacial Catalyst for the Hydrolysis of Triglycerides. Issue 17 (23rd August 2017) - Shi, Hui; Fan, Zhaoyu; Hong, Bing; Pera‐Titus, Marc
Abstract: Rational design of the surface properties of heterogeneous catalysts can boost the interfacial activity in biphasic reactions through the generation of Pickering emulsions. This concept, termed Pickering interfacial catalysis (PIC), has shown promising credentials in acid‐catalyzed transesterification, ester hydrolysis, acetalization, etherification, and alkylation reactions. PIC has now been applied to the efficient, solvent‐free hydrolysis of the triglyceride glyceryl trilaurate to lauric acid, catalyzed by Aquivion perfluorosulfonic superacid at mild conditions (100 °C and ambient pressure). Abstract : Superacid, super catalyst : Rational design of the surface properties of heterogeneous catalysts can boost the interfacial activity in biphasic reactions through the generation of Pickering emulsions, a phenomenomenon through which Aquivion perfluorosulfonic superacid catalyzes the efficient, solvent‐free hydrolysis of glyceryl trilaurate at 100 °C and ambient pressure.